Increasing Growth and Natural Regeneration of Teak - Takle, G. G.; Mujumdar, R. B. (Indian Forester, 1956)
The paper deals with distribution of teak in Madhya Pradesh with reference to climate, elevation, geology and soil. The forests in which teak occurs in fair proportion have been termed as mixed teak forests. They conform to the southern tropical dry and moist deciduous types of forests of Champion's Classifications. The growing stock varies from open low quality forests of almost pure teak in the areas with annual rainfall of 30 inches to better stocked high quality forests. The suitability of teak to the soils derived from trap rock under the climatic conditions has been discussed.